2020
DOI: 10.15252/embr.201949499
|View full text |Cite
|
Sign up to set email alerts
|

Myf6/MRF4 is a myogenic niche regulator required for the maintenance of the muscle stem cell pool

Abstract: The function and maintenance of muscle stem cells (Mu SC s) are tightly regulated by signals originating from their niche environment. Skeletal myofibers are a principle component of the Mu SC niche and are in direct contact with the muscle stem cells. Here, we show that Myf6 establishes a ligand/receptor interaction between muscle stem cells and their associated muscle fibers. Our data show that Myf6 transcriptionally regulates a broad spectrum of myokines and mus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…To further assess the quality of the ATAC-Seq data, we analyzed select genes that are expressed by either MuSCs or myofibers. For instance, in the myofiber samples, we confirmed the presence of ATAC-seq peaks in the promoter regions of Ckm , Actin alpha 1 ( Acta1 ), Myogenic factor 6 ( Myf6 ) and Myosin heavy chain 4 ( Myh4 ), all of which are expressed by myofibers but not MuSCs (14,47,49,50) (Figure 2I-L). On the other hand, in MuSCs we observed peaks in the promoter regions of Paired box 7 ( Pax7 ), and Myf5, genes that are known to be expressed in MuSCs (48, 51) (Figure 2M-N).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…To further assess the quality of the ATAC-Seq data, we analyzed select genes that are expressed by either MuSCs or myofibers. For instance, in the myofiber samples, we confirmed the presence of ATAC-seq peaks in the promoter regions of Ckm , Actin alpha 1 ( Acta1 ), Myogenic factor 6 ( Myf6 ) and Myosin heavy chain 4 ( Myh4 ), all of which are expressed by myofibers but not MuSCs (14,47,49,50) (Figure 2I-L). On the other hand, in MuSCs we observed peaks in the promoter regions of Paired box 7 ( Pax7 ), and Myf5, genes that are known to be expressed in MuSCs (48, 51) (Figure 2M-N).…”
Section: Resultssupporting
confidence: 53%
“…The GSEA between uninjured myofibers and MuSCs revealed that one of the top significantly enriched pathways is myogenesis where we can observe that genes associated with differentiation and myofiber function such as Myf6 , Ckm and Tropomyosin 2 ( Tpm2 ) (14,47,60,61) have higher accessibility in the myofiber compared to MuSCs (Figure 5B-5D). On the other hand, genes associated with quiescence and MuSCs such as alpha 7 integrin ( Itga7 ) and Gpx3 are more accessible in MuSCs compared to the myofiber, as expected (62, 63) (Figure 5C, 5E).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1) [13,18]. Finally, the formation of multinucleated myofibers results in the decreased expression of MYOD1 while MYF6/MRF4 becomes highly expressed in the functional muscle fiber [19][20][21].…”
Section: Muscs Mediate Regeneration Of Skeletal Musclementioning
confidence: 99%
“…Skeletal muscle satellite cells (MuSCs) are known to be an essential cell population for muscle regeneration, and are activated upon muscle injury and undergo multiple progenitor cell stages until differentiating into myofibers. In this process of muscle regeneration, there is also a self-renewing state in which MuSCs again transition to a quiescent state and refill the MuSC pool 15,16 . Therefore, we attempted to characterize heterogeneous cell populations of MuSCs with multiple transient states by DFC, which has been difficult to capture by a DEG-based approach.…”
Section: Resultsmentioning
confidence: 99%